Ability to control forehand groundstroke of skilled tennis players - Furuya, R.; Dimic, M.; Vogt, T.; Kanosue, K.; Nakata, H. (PLOS ONE, 2025)
In tennis, the ability to hit groundstrokes accurately to a target area on the court is important. It is a common belief in tennis coaching that greater concentration leads to more accurate targeting. The purpose of this study was to test this belief by evaluating the variability of the ball-landing position when hitting toward target areas of different sizes and locations. Ten male top-level college tennis players performed forehand strokes and aimed at four target areas: 1) a short area (Short) between the service line and baselines, and 2) a deep area (Deep) just inside the baseline, both with an identical target size (2*2 m); and 3) a large area (Big, 2*4 m), and 4) a small area (Small, 1*1m), both centered in the same location. The average ball-landing position, standard deviation (SD), and bivariate variable error (BVE) were calculated. SD and BVE were normalized relative to the distance between the player and center of the target area. SD in the depth direction (net-baseline direction) was significantly smaller in Short than Deep, but the normalized SDs showed no difference. SD in Big was not significantly different from that in Small, suggesting that it is inherently difficult even for advanced tennis players to intentionally control the distribution of their ball-landing positions.